Arte e identidad en la Europa de entreguerras: el Salon d’Automne y la Exposition des artistes catalans de 1920 - Eva March (Mélanges de la Casa de Velázquez, 2025)
This article studies the Exposition des artistes catalans held at the 1920 Salon d’Automne in Paris from the perspective of the political use of art. It centres its attention on examining the strategies developed by a local administration, the Barcelona City Council, to position the Catalan specificity internationally through a major art event. The analysis of the unpublished documentation confirms that, far from being considered a simple cultural artefact, the exhibition of Catalan artists in Paris, like the exhibitions held in Europe during the inter-war period, should be understood as a platform for exporting national values, as effective instruments used by cultural diplomacy to project national artistic capital abroad. And that this happened even though their main actors were, as in the Catalan case, secondary agents on the European geopolitical chessboard.